Uso de redes sociales y comportamientos adictivos en adolescentes - Balcázar Abad, Sandra Gabriela (2024)
In the transition period of a adolescent' life, their emotional, social, cognitive and physical skills can be develop more quickly, that is why at this stage adolescents must face a series of challenges y presures to be able to perform in different areas. For these reasons, adolescents sometimes look for a way avoid such challenges and look for easier way out as immersing in the networks and becoming addicted to them. The general objetive of this research was to analyze the scientific evidencie about the influence of the use of social networks on addictive behaviors in adolescents. For this purpose, an exploratory and descriptive bibliographic research was carried out with a qualitative approach and no-experimental design that included 80 articles, of which 40 were eliminated due to duplication, and 10 were discarded according to the exclusion criteria, thus obtaining 35 articles in the selection stage, through which 10 were omitted due to incomplete information. In this way, it worked with 25 articles that were used in this scientific research in the Spanish language with a reference of 13 years old. Ultimately, it can be stated that social networks and addictive behaviors can unchain both negative and positive impacts on their emotional, social, cognitive and physical skills and this produces addiction to them, which will make teenagers obsessed and thus make them addicted and thus make them addicted, letting them get away from reality without allowing them to see what is happening in the different areas